Report for the Year 1974 - University Grants Commission, Bangladesh (Dacca : Bangladesh, 1974)
The 1974-75 annual report of the University Grants Commission (UGC), New Delhi, India, is presented. Contents pertain to: institutions and enrollment in higher education; approach to fifth plan development of universities and colleges; development of universities; development of colleges; students; faculty improvement programs; cultural exchange programs and international collaboration; support for research; and maintenance and coordination of standards. The Commission took various measures to regulate expansion of students, particularly at the undergraduate stage. The expansion of higher education for 1974-75 was 5.9 percent as compared to 12-14 percent during the sixties. The amended UGC Act, effective June 17, 1972, has helped to bring about restraint in the establishment of new universities and colleges. In 1974-75, 85 new colleges were established as compared to 152 new colleges established during 1973-74. The Commission is taking steps to strengthen science teaching in undergraduate colleges and to revise the syllabi. (SW)
Microfiche.
Keywords: Higher Education; India; University Grants Commission (New Delhi); Reports, Descriptive